Bangladesh studies : politics, administration, rural development, and foreign policy - Khan, Mohammad Mohabbat, 1949-; Hosena, Saiẏada Ānoẏāra, 1934-; University of Dacca. Centre for Administrative Studies (Dhaka : Center for Administrative Studies, University of Dhaka, 1985)
Deliberations of a workshop organized by the Centre for Administrative Studies, University of Dacca.
Includes bibliographies.
Keywords: Bangladesh -- Politics and government; Rural development -- Bangladesh